The interaction of Apolipoprotein A5 gene promoter region T-1131C polymorphism (rs12286037) and lifestyle modification on plasma triglyceride levels in Japanese - Yamasaki, Masayuki (Nutr Res Pract, 2015)
BACKGROUND/OBJECTIVE: Apolipoprotein A5 gene promoter region T-1131C polymorphism (APOA5 T-1131C) is known to be associated with elevated plasma TG levels, although little is known of the influence of the interaction between APOA5 T-1131C and lifestyle modification on TG levels. To investigate this matter, we studied APOA5 T-1131C and plasma TG levels of subjects participating in a three-month lifestyle modification program. SUBJECTS/METHODS: A three-month lifestyle modification program was conducted with 297 participants (Age: 57 ± 8 years) in Izumo City, Japan, from 2001-2007. Changes in energy balance (the difference between energy intake and energy expenditure) and BMI were used to evaluate the participants' responses to the lifestyle modification. RESULTS: Even after adjusting for confounding factors, plasma TG levels were significantly different at baseline among three genotype subgroups: TT, 126 ± 68 mg/dl; TC, 134 ± 74 mg/dl; and CC, 172 ± 101 mg/dl. Lifestyle modification resulted in significant reductions in plasma TG levels in the TT, TC, and CC genotype subgroups: -21.9 ± 61.0 mg/dl, -20.9 ± 51.0 mg/dl, and -42.6 ± 78.5 mg/dl, respectively, with no significant differences between them. In a stepwise regression analysis, age, APOA5 T-1131C, body mass index (BMI), homeostasis model assessment-insulin resistance (HOMA-IR), and the 18:1/18:0 ratio showed independent association with plasma TG levels at baseline. In a general linear model analysis, APOA5 T-1131C C-allele carriers showed significantly greater TG reduction with decreased energy balance than wild type carriers after adjustment for age, gender, and baseline plasma TG levels. CONCLUSIONS: The genetic effects of APOA5 T-1131C independently affected plasma TG levels. However, lifestyle modification was effective in significantly reducing plasma TG levels despite the APOA5 T-1131C genotype background.